Macroeconomic effects of Interest Rate in Nigeria: A Rolling Impulse Response Approach - Olanrele, Iyabo Adeola; Angahar, Jacob Sesugh (International Journal of Humanities, Education, and Social Sciences, 2025)
The study examines the macroeconomic effects of interest rate shocks in Nigeria using a rolling impulse response method within a structural vector autoregressive (SVAR) framework. It fills a gap in understanding how interest rate fluctuations affect key economic indicators, including GDP growth, inflation, and exchange rate (EXC), by assessing their reactions to interest rate changes over various time periods. Results indicate that interest rate shocks significantly influence GDP growth, inflation, and exchange rate initially, with these effects fading within 4-6 months. The varied responses across different periods reflect changing economic conditions. The study suggests that policymakers should adopt a flexible approach to interest rate management, considering the current economic context. Additionally, ongoing monitoring of how key economic indicators react to interest rate changes is essential for effective policy development.